Direction Of The Causal Relationship Between Construction And The National Economy Of Sri Lanka - Ramachandra, Thanuja; Rotimi, James Olabode Bamidele; Rameezdeen, Raufdeen (Penerbit Universiti Sains Malaysia, 2013)
Causal relationships between construction and national economies have received considerable attention in the past. However, the results of research on this topic provide contrasting views about the nature of the relationship. This paper investigates the direction of the causal relationship between construction and the economy of a developing country, Sri Lanka, using empirical data for selected economic and construction indicators for the period 1990 to 2009. The pattern of the causal relationship was determined using the Granger causality test. The findings reveal that national economic activities precede construction activities for all indicators except construction investment. The study therefore concludes and strengthens the body of knowledge concerning the causal relationship between the construction sector in Sri Lanka and the national economy tending towards a uni-directional relationship, with the national economy inducing growth in the construction sector and not vice versa.